Meningkatkan Kemampuan Pengucapan Huruf Vokal Melalui Metode Multisensori Pada Siswa Tunarungu - Ayu Anisa; Martias Z (Jurnal Penelitian Pendidikan Khusus, 2022)
This study discusses improving the pronuonciation of vowels through multisensory methods for hearing impairment student. The subject of this study was a hearing impairment student of class II SLB Negeri 2 Pariaman. This research uses a quantitative approach with a type of Single Subject Reseacrh with A-B-A design. Data collection is done through observations, interviews, tests, and documentation. Data gathering tools using research instruments. The data of the study results are analyzed using graphs. Based on the results of the study it was stated that the pronunciation of hearing impairment student' vowels increased after being given intervention by multisensory methods.